Do Young Professionals in Malaysian Urban Areas Prioritise Sustainability When Making Housing Decisions? - Nor Suzylah Sohaimi; Syafiee Shuid (Journal of Contemporary Urban Affairs)
The present study delves into the decision-making processes pertaining to housing among young professionals residing in urban areas, focusing particularly on their preferences for sustainable housing options. Understanding the factors influencing the housing preferences of this demographic is critical for promoting sustainable urban development, given the ongoing challenges of urbanisation and environmental issues faced by cities. This study aims to explore the decision-making process pertaining to housing among young professionals in Malaysian urban areas and its correlation with sustainability. This study employs a mixed-methods approach, encompassing surveys and in-depth interviews, to analyse the significant factors and decision-making criteria of young professionals residing in urban settings concerning housing. This study primarily focuses on the economic aspect of housing decisions, specifically home affordability, without dismissing the social and environmental factors that may also influence these decisions. The present study contributes to the ongoing discourse on urban sustainability by elucidating the dynamic and evolving preferences of young professionals residing in urban areas. The findings provide valuable insights for politicians, urban planners, and developers who aim to construct housing options that are both sustainable and appealing to this influential demographic group. Ultimately, this contributes to the overall sustainability and resilience of urban communities.